Collaboration, Compliance, and Cupcakes: A Classroom Exercise. (June 2023) - Boehler, Barbara-Ann; MacLean, Tammy; O'Neill, Regina
This in-class, 75-minute exercise creates a context for students to observe some of the challenges to cross-functional collaboration and offers insight into processes to achieve more successful outcomes. By demonstrating how a failure by compliance and business operations to work cross-functionally negatively impacts outcomes in the form of misaligned and ineffective corporate compliance procedures, students learn firsthand the importance of cross-functional collaboration. Given the ubiquity and importance of corporate ethics and compliance programs, this exercise fills an important pedagogical gap in management education.